Between film, video, and the digital hybrid moving images in the post-media age - Kim, Jihoon (International texts in critical media aesthetics, 2018)
"A wide-ranging theoretical and aesthetic exploration of hybrid moving images based on the intersection of film, video, and digital technology"--